Combining semantic word classes and sub-word unit speech recognition for robust OOV detection - Horndasch, Axel; Batliner, Anton; Kaufhold, Caroline; Nöth, Elmar (17th Annual Conference of the International Speech Communication Association (INTERSPEECH 2016): Understanding Speech Processing in Humans and Machines, 2016)
Out-of-vocabulary words (OOVs) are often the main reason for the failure of tasks like automated voice searches or human-machine dialogs. This is especially true if rare but task-relevant content words, e.g. person or location names, are not in the recognizer's vocabulary. Since applications like spoken dialog systems use the result of the speech recognizer to extract a semantic representation of a user utterance, the detection of OOVs as well as their (semantic) word class can support to manage a dialog successfully. In this paper we suggest to combine two well-known approaches in the context of OOV detection: semantic word classes and OOV models based on sub-word units. With our system, which builds upon the widely used Kaldi speech recognition toolkit, we show on two different data sets that - compared to other methods - such a combination improves OOV detection performance for open word classes at a given false alarm rate. Another result of our approach is a reduction of the word error rate (WER).
Keywords: OOV detection and classification; Kaldi; Sub-word unit speech recognition; Semantic word classes

FAUBOT: Purposeful Navigation of a Robot in a Simulated Environment - Danner, Daniel; Kaufhold, Caroline; Kranz, Peter; Müller, Rainer; Pfaller, Sven; Riess, Christian; Angelopoulou, Elli (28th IEEE International Real-Time Systems Symposium (RTSS 2007), 2007)

How to add word classes to the Kaldi speech recognition toolkit - Horndasch, Axel; Kaufhold, Caroline; Nöth, Elmar (Text, Speech, and Dialogue. TSD 2016, 2016)
The paper explains and illustrates how the concept of word classes can be added to the widely used open-source speech recognition toolkit Kaldi. The suggested extensions to existing Kaldi recipes are limited to the word-level grammar (G) and the pronunciation lexicon (L) models. The implementation to modify the weighted finite state transducers employed in Kaldi makes use of the OpenFST library. In experiments on small and mid-sized corpora with vocabulary sizes of 1.5 K and 5.5 K respectively a slight improvement of the word error rate is observed when the approach is tested with (hand-crafted) word classes. Furthermore it is shown that the introduction of sub-word unit models for open word classes can help to robustly detect and classify out-of-vocabulary words without impairing word recognition accurac
Keywords: OOV detection and classification; Kaldi speech recognition toolkit; Word classes

PATSY-I: A Corpus on Non-Native English Air Traffic Communication - Kaufhold, Caroline; Martindale, Christine; Horndasch, Axel; Reinhard, Klaus; Nöth, Elmar (Tagungsband der 12. Tagung Phonetik und Phonologie im deutschsprachigen Raum, 2016)
In many global tasks English is used as an international language. As a consequence, non-native speakers of the English language often communicate with other non-native speakers. An example is the Air Traffic Control (ATC) service which directs aircrafts on the ground and through controlled airspace. It is of course essential that there is a perfect understanding between the pilot and the ground-based controller to prevent collisions and to organize air traffic efficiently. Aviation English already accommodates non-native speakers of English by providing guidelines for wording and phraseology. To avoid confusion, for example, letters and numbers are spelled according to the international spelling alphabet provided by the International Civil Aviation Organization (ICAO). However, the ability to speak and understand English still has a high impact on communication success. In this paper, we present a corpus that was recorded in the context of the ATC phraseology training system PATSY, the prototype of which was presented at the Show&Tell session at Interspeech 2015. The corpus consists of basic ATC utterances by speakers of 16 different mother tongues. Furthermore, "Please Call Stella" and part of "The Rainbow Passage" were recorded twice for every speaker with different biases. We plan on using this data to study the entrainment effect, which was observed for conversations by Levitan and Hirschberg. Preliminary results on basic ATC utterances show a moderate correlation between the speakers' self-assessment and the GoP (Goodness of Pronunciation) score.<br
Keywords: English as Lingua Franca (ELF); Computer Assisted Pronunciation Training (CAPT); Accent Entrainment

PATSY - It's all about pronunciation! - Kaufhold, Caroline; Gamidov, Vadim; Kiessling, Andreas; Reinhard, Klaus; Nöth, Elmar (16th Annual Conference of the International Speech Communication Association, INTERSPEECH 2015, 2015)
PATSY is an abbreviation for its German name "Piloten/ATC Trainingssystem für den Sprechfunk" which translates to pilot/ air traffic control (ATC) training system for radio communication. The phraseology training system is intended to be a stand-alone, platform-independent, multi-user e-Learning framework for learning and practicing the ATC radio communication wordings and at the same time improving intelligibility of the speaker by pronunciation scoring. A serious gaming approach is aimed at, which allows the user to practice his or her communication skills in almost real-life scenarios. At the Show and Tell session at Interspeech 2015, we would like to present a subsystem of PATSY in which we only concentrate on pronunciation scoring. The speaker is prompted to record a sequence of words of the NATO phonetic alphabet and he is given back a visually enhanced feedback regarding his pronunciation score. Further aspects of PATSY are the verification of correct syntax and the assessment of the speaker's "comfort level" which states how familiar the speaker is with the topic in question.
Keywords: Augmented learning; Computer Assisted Pronunciation Training (CAPT); Pronunciation scoring

Reliable Detection of Important Word Boundaries Using Prosodic Features - Kaufhold, Caroline; Stemmer, Georg; Nöth, Elmar (Springer-verlag, 2011)
Natural input dialog systems for entering address data in modern GPS units demand a significantly more robust extraction of slot information. In previous work, prosody was used to detect phrase boundaries (PB) which separate particular address parts. Only input without filler words was used. In this work, carrier sentences are allowed. A boosting approach provides twenty strong prosodic features which model the characteristic of PBs. We introduce the concept of a prosodically marked word boundary (PMB), which enables a better location of the provided information in natural input. Our results on a dataset of 5883 input samples reveal that about 67% of the found PBs indicate a PMB, while most of the remaining boundaries occur within compound words.
Keywords: prosody; phrase boundary detection; multi-slot input modality